Against Expediency: The Ethics of Education - Mannion, Gerard (Catholic Education: A Journal of Inquiry and Practice, 2007)
This article suggests that church-linked universities and colleges can and should show that there is an alternative to the expediency and pseudo-utilitarian thinking which currently dominates higher education. Such institutions can and should serve as beacons of a virtuous approach to education which can show others a more positive way forward. Theology and ethics”both disciplines mutually informing the other”hold the key to fostering and promoting a true culture of ministry both in the day-to-day existence of universities and colleges and in nurturing young minds to take that culture of ministry out into the wider community.